Valorisation of sweet potato leaves as a potential agri‐food resource: Assessing nutritional and nutraceutical values altered by food processing—A review - Yi, Junpeng; Li, Luyao; Li, Xin; Duan, Xu; Wang, Junling; Han, Yuxin; Gao, Yan (International journal of food science & technology, 2024)
Summary Sweet potato leaves are rich in nutrients and bioactive substances. They are commonly utilised as human foodstuff in some Asian, African and North American countries. Leafy vegetables are generally processed through domestic cooking or industrial processing techniques before consumption. This paper reviews the available literature on the nutritional composition and phytochemical profile, along health benefits of processed sweet potato leaves. Discussion on the applications of sweet potato leaves as a valuable fortifying ingredient in a variety of food formulations is included. Domestic cooking resulted in a substantial increase in protein content at optimal conditions but led to a significant loss of bioactive compounds. Vacuum freeze‐drying retained most of nutrients and caffeoylquinic acid derivatives. Fermentation and supplementation as fortifying ingredients in food formulations could improve the nutritional status and sensory characteristics of the final products. This review can facilitate the development of an integrated plant for the valorisation of sweet potato agro‐industrial residues and aid the food industry in obtaining fortified foods with sweet potato leaf loaded. In this paper, the available literature on the nutrient composition, phytochemicals and health benefits of processed sweet potato leaves is reviewed, and the use of sweet potato leaves as a valuable fortification ingredient in various food formulations is also discussed.